Development of Cheerful Interactive Multimedia (MIC) in Science Subjects for Class V SD KIP V Bara-Baraya Makassar City. - Nurfikriani Eka Putri; Suarlin Suarlin; Andi Makkasau (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2026)
The goal of this research is to determine whether cheerful interactive multimedia (MIC) can be used in science classes for fifth-grade students at KIP V Bara-Baraya  elementary school, Makassar City. This research develops products based on the results of an analysis of student needs using research and development (R&D) types. The research subjects were 20 students in class 5A, and the research and development procedure used was the Alessi & Trollip development model, which began with the planning stage, the design stage, and the development stage. Products developed through additional research go through two stages of testing: alpha and beta. The alpha test or validity test in this study involved two validators, namely the material expert validator and the media expert validator. Based on the results of the media expert validation analysis, an overall score of 93 was obtained with a percentage of 83.03%, so multimedia products are in the "very eligible" category. The results of the material expert validation analysis obtained an overall score of 70 with a percentage of 92.10%, so multimedia products are in the "very eligible" category. As for the results of the responses of students and teachers for each product, they obtained percentages of 92.9% and 93.05%, so that multimedia products were in the "very eligible" category. Based on the results of this study, it can be an additional reference for future researchers and an innovation in developing interactive multimedia in elementary schools.